Cyclometalated titanium and zirconium complexes stabilised by a new silylmethylene-linked tetradentate triamidophosphine - Sietzen, Malte; Federmann, Patrick; Wadepohl, Hubert; Ballmann, Joachim (Dalton transactions, 2016)
The silylmethylene-linked triamidophosphine P(CH2SiMe2NHPh)3 was isolated in form of its tri-lithium salt Li3[P(CH2SiMe2NPh)3]·2.5Et2O (1·2.5Et2O) and employed for the synthesis of titanium and zirconium complexes. Starting from 1·2.5Et2O, the chlorido complexes [κ4-N,N,N,P-PN3]MCl (4-M, M = Ti, Zr) were prepared and examined with respect to alkylation. Upon reaction of 4-Ti with (trimethylsilyl)methyl lithium, intra-ligand cyclometalation at one of the ortho-N-phenyl positions was observed and the resulting thermally stable titanazetidine [κ5-N,N,N,P,C-N2P(NC)]Ti (5-Ti) isolated. Similarly, the related zirconazetidine [κ5-N,N,N,P,C-N2P(NC)]Zr(THF) (5-Zr) was isolated upon reaction of 4-Zr with Bn2Mg(THF)2. Using LiCH2PMe2 as alkyl transfer reagent, both complexes 4-M were converted to the corresponding phosphametallacyclopropanes [κ4-N,N,N,P-PN3]M(κ2-C,P-CH2PMe2) (7-M, M = Ti, Zr). Upon gentle heating, complexes 7-M were cleanly converted to the cyclometalated species 5-M and trimethylphosphine. These results are discussed in the context of related amidophosphine and triamidoamine complexes.